Implementation of Scientific Spirit Education based on the History of Natural Science - Yongli Xing, Shixiang Zou (Forest Chemicals Review, 2022)
Relying on the history of natural science, this paper explores the scientific spirit, scientist spirit, and philosophical and dialectical materialist thoughts contained in the major scientific discoveries and achievements made in the modern history of global science development, in order to explore how to integrate the matter-of-fact scientific attitude, the spirit of rationality, the spirit of exploration and innovation, into classroom activity. In the process of knowledge imparting, typical cases recorded in the history of science can be used to implement scientific spirit education in order to fulfill the goal of fostering virtues through education and helping students establish a correct outlook on life, worldview, and values, with a goal of cultivating both people and talent.